Customer awareness towards promotional activities on ASNB products: Perspective on students of Sekolah Menengah Kebangsaan Durian Daun, Melaka / Norasyida Zaihana Abd Shukor - Abd Shukor, Norasyida Zaihana (Faculty of Business and Management, 2008)
The purpose of the study are to determined the levels of awareness of respondents about ASNB Products, to identify the most effective awareness tools use by Amanah Saham Nasional Berhad (ASNB), and if the promotional tools employ by PNB are effective. Based on Pickton, David & Broderick, Amanda (2005) , customer awareness can be creating due to reach, choices of media, frequency of campaign and continuity. Customer awareness among the students at Melaka is still low compared to the other state in Malaysia. According to the situation, the researcher has chosen 185 students from Sekolah Menengah Kebangsaan Durian Daun, Melaka to be the respondents. In this study, the researcher has used exploratory, descriptive and causal research. Self administered questionnaire has been used in order to collect data from the respondents. Reliability test, frequency of distribution, cross tabulation, hypotheses, correlation and regression has been used in this study to get the data from the questionnaire that been distributes to the respondents by using the Statistical Package for Social Science (SPSS). Finally, from the finding, it shows that choices of media is the influence factors that can create awareness among the students of Sekolah Menengah Kebangsaan Durian Daun, Melaka basically, but it can be used also towards all students in Melaka especially. The choices of media are also related with the other factors such as reach, frequency of campaign and continuity.